Moderating Effect of Application of Accounting Technology on Audit Quality - Akinola, Amos O.; Daramola, Peter S.; Adenle, Timilehin E. (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2025)
This study examines the moderating effect of accounting technology (AT) on audit quality. Primary data were sourced from hundred and fourteen auditors in private practice using a questionnaire drawn on a four-point Likert scale. Both the internal reliability and validity of the instrument were established. Three hundred and eighty-nine participants filled and returned, while three hundred and sixty two were found valid for the study and subjected to analysis using a regression model to test hypotheses one and two while the third hypothesis was subjected to LSM-SEM. The results of the analysis show that there is a positive significant (R2 = 0.554, Pvalue = 0.000) moderating effect of AT on the technical quality of audits and on the service quality of audits (R2 = 0.840, p-value = 0.000). The joint moderating effect of AT was found to have a substantial, positive, and significant effect (adjusted R2 of 0.849, Pvalue = 0.000) on audit quality, while Q2 of 0.540 established the fact that there is a large degree of relevance of the structural model employed for the joint effect. It is therefore recommended that standard-setting boards provide the necessary guidelines to drive audit quality in this era of accounting technology. Additionally, there is a need to conduct studies with a wider scope across regions.